CATALYST: challenging antibiotic allergy status. (28th March 2023) - Brayson, Joseph; Barrett, Scott; Baqir, Wasim; Campbell, David; Oswald, Tamsin; Ellis, Simon; Premchand, Nikhil
Abstract: Objectives: To develop a transferable process, CATALYST (c hallenging a nt ibiotic al lergy st atus), to assess and challenge penicillin allergy status of inpatients within an NHS Foundation Hospital. Methods: A multidisciplinary team (MDT) steering group reviewed existing literature and protocols enabling penicillin allergy assessment, challenge and de-labelling. Using this, they identified five key steps forming the basis of CATALYST: clinical assessment of the nature of allergy; inclusion/exclusion criteria; consent; direct oral penicillin challenge; and removal of allergy label. A pharmacist-led pilot was conducted to assess the process, during which a continuous PDSA (plan-do-study-act) cycle was observed. This included formally auditing endpoint data such as accuracy of allergy status in medical records post-intervention. Results: CATALYST was successfully developed with key resources produced to support clinicians. It was piloted in 304 patients, with 172 patients excluded and 132 successful allergy challenges. There was one incident of an adverse event (acute kidney injury) in the 132 successful patients, which occurred as a delayed reaction following 22 days of penicillin therapy. Only 64% of permanent records (held by GP) were appropriately updated when audited at the end of the pilot. Conclusions: CATALYST is a transferable process to facilitate safe assessment, challenge and removal of spurious penicillin allergy labels. Handover between care sectors forms a key element of allergy removal to ensure all records are updated and work is needed to ensure this process is done effectively.